A Holistic Systems Approach to Characterize the Impact of Pre- and Post-natal Oxycodone Exposure on Neurodevelopment and Behavior - Odegaard, Katherine E.; Schaal, Victoria L.; Clark, Alexander R.; Koul, Sneh; Sankarasubramanian, Jagadesan; Xia, Zhiqiu; Mellon, Melissa; Uberti, Mariano; Liu, Yutong; Stothert, Andrew; Van Hook, Matthew; Wang, Hanjun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Increased risk of oxycodone (oxy) dependency during pregnancy has been associated with altered behaviors and cognitive deficits in exposed offspring. However, a significant knowledge gap remains regarding the effect of in utero and postnatal exposure on neurodevelopment and subsequent behavioral outcomes. Methods: Using a preclinical rodent model that mimics oxy exposure in utero (IUO) and postnatally (PNO), we employed an integrative holistic systems biology approach encompassing proton magnetic resonance spectroscopy (1H-MRS), electrophysiology, RNA-sequencing, and Von Frey pain testing to elucidate molecular and behavioral changes in the exposed offspring during early neurodevelopment as well as adulthood. Results: 1H-MRS studies revealed significant changes in key brain metabolites in the exposed offspring that were corroborated with changes in synaptic currents. Transcriptomics analysis employing RNA-sequencing identified alterations in the expression of pivotal genes associated with synaptic transmission, neurodevelopment, mood disorders, and addiction in the treatment groups. Furthermore, Von Frey analysis revealed lower pain thresholds in both exposed groups. Conclusions: Given the increased use of opiates, understanding the persistent developmental effects of these drugs on children will delineate potential risks associated with opiate use beyond the direct effects in pregnant women.